Antibiotic Prescribing for Dental Procedures in Community-Associated Clostridium difficile cases, Minnesota, 2009–2015. (4th October 2017) - Bye, Maria; Whitten, Tory; Holzbauer, Stacy
Abstract: Background: Clostridium difficile infections (CDIs) are the leading cause of healthcare-associated diarrhea. Two of the most significant risk factors for CDI are antibiotic use and healthcare exposure. Dentists write approximately 10% of all outpatient prescriptions in the USA; however, limited data are available regarding dental prescribing's impact on CDI. We described characteristics of community-associated (CA) CDI cases following antibiotics for dental procedures. Methods: The Minnesota Department of Health (MDH) performs active population- and laboratory-based surveillance for CDI as part of the CDC's Emerging Infections Program (EIP). A case was defined as a positive C. difficile toxin or molecular assay on a stool specimen from a person >1 years old without a positive test in the prior 8 weeks, living in one of the five EIP catchment counties. Cases were classified as CA if stool was collected ≤3 days of admission or as an outpatient, with no overnight stay in a healthcare facility in the past 12 weeks. Medical records were reviewed and interviews performed to assess CDI risk factors and potential exposures. Differences in antibiotic prescribing and documentation among CA CDI cases receiving dental procedures were explored. Results: During 2009–2015, 2176 presumptive CA CDI cases were reported to MDH; 1626 (75%) were confirmed as CA and interviewed. In total, 926 (57%) were prescribed antibiotics and 136 (15%) for dental procedures. Cases prescribed antibiotics for dental procedures were significantly older (median age: 57 vs. 45 years, P  < 0.001), more likely to be prescribed clindamycin (50% vs. 10%, P  < 0.001), and less likely to be prescribed fluoroquinolones (6% vs. 19%, P  < 0.001) and cephalosporins (7% vs. 30%, P  < 0.001) than those prescribed antibiotics for other indications. Among cases who received antibiotics for a dental procedure, 31 (23%) reported antibiotics on interview which were also documented in the medical record and 46 (34%) reported antibiotics for any reason on interview without documentation in the medical record. Conclusion: Dental antibiotic prescribing rates are likely underestimated. Stewardship programs should address dental prescribing and alert dentists to CDI subsequent to antibiotics prescribed for dental procedures. Disclosures: All authors: No reported disclosures.